Idiopathic Intracranial Hypertension in a pubertal paediatric Indian patient - Aggarwal, Anand; Kaur, Prempal; Chhabra, Kanika; Singh, Karamjit; Goyal, Piyush (Nepalese Journal of Ophthalmology, 2017)
Background: Idiopathic Intracranial Hypertension (IIH) is characterised by raised intracranial pressure (ICP) with normal cerebrospinal fluid (CSF) composition and absence of hydrocephalus or space occupying lesions. IIH is a rare disease in children. It can lead to visual impairment but prompt diagnosis and treatment in most of the cases will prevent potentially permanent visual loss. Objective: To report a rare case of Idiopathic Intracranial Hypertension in a pubertal child, clinical features, and findings of Magnetic Resonance Imaging (MRI) and visual field of this case. Case: An adolescent girl aged 14 years presented with headache and transient visual obscuration for two weeks. On examination, findings (fundus, visual field and MRI) were suggestive of Idiopathic intracranial hypertension. She did not have any classical predisposing risk factors. She recovered very well with acetazolamide and short term steroid therapy with no sequelae and clinical recurrence over a follow up of 12 months. Conclusion: This is a rare case of IIH in a child, which was confirmed on the MRI and visual field testing.